Решить (4x^2+y^2-(2x-y)^2): 4x/8x^2y

Anna45891 Anna45891    3   21.07.2019 08:06    0

Ответы
PolinaChery04 PolinaChery04  23.09.2020 07:21

Объяснение:

(4х^2 +у^2 -(2х-у)^2)÷4х/(8х^2 у)=(4х^2 +у^2 -4х^2 +4ху-у^2)•2ху=4ху•2ху=8х^2 у^2=8(ху)^2

ПОКАЗАТЬ ОТВЕТЫ
kaaaarrrr kaaaarrrr  23.09.2020 07:21

ответ:  8х²у².

(4x^2+y^2-(2x-y)^2) : \frac{4x}{8x^2y} = (4x^2+y^2-(4x^2-4xy+y^2)) : \frac{1}{2xy} = \\\\= (4x^2+y^2-4x^2+4xy-y^2)*2xy= (4xy)*2xy = 8x^2y^2.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра